Improving Students’ Speaking Skill through Communication Game, Recorded Role Play and Peer Feedback - Arismayang, Friska (University of Muhammadiyah Prof. DR. HAMKA, 2016)
This study aims to improve students’ speaking skills using the combined strategies of communication game, recorded role play and peer feedback activities. This action research took place at an English institution in Jakarta, Indonesia and collected the data by observing the learning process with the collaborator, analyzing the video during the class, making field notes, conducting tests (pretest and post test) and interviewing students. There were three cycles in this study. Results of the tests showed that students’ speaking skills improved. The mean score of pre-test was 3.1, while the mean score of post-test in cycle one was 3.3, cycle two 3.5 and cycle three 3.6. Based on the interview, all students were interested in and excited about the use of the three strategies above. However, there was a problem with the implementation of peer feedback activities; it was time consuming. The results of this study can not only promote an idea for EFL teachers to use the strategies as an alternative approach to teaching speaking skills but also inspire EFL teachers to be more creative in using these three strategies.